Pengaruh Konsentrasi NaOH terhadap Kadar Air Kertas Berbahan Dasar Daun Mahkota Nanas - Aulia Firdaus Syazidan; Emmidia Djonaedi; Rachmah Nanda Kartika (Pusat riset dan Inovasi Nasional, 2025)
Agricultural waste such as pineapple crown leaves (Ananas comosus) has not been optimally utilized, despite its high cellulose fiber content, making it a potential alternative raw material for paper production. One of the main challenges in this process is controlling the paper's moisture content, as excessive water content can reduce product quality. This study aims to investigate the effect of sodium hydroxide (NaOH) concentration on the moisture content of paper made from pineapple crown leaf fibers. Three NaOH concentrations (2%, 8%, and 14%) were applied during the pulping process to remove lignin and hemicellulose, followed by gravimetric analysis of the resulting paper’s moisture content. The results showed that the 8% NaOH treatment produced the lowest moisture content of 8.35%, while the 2% NaOH treatment resulted in the highest moisture content of 10.34%. One-way ANOVA indicated that variations in NaOH concentration had a statistically significant effect on moisture content (p < 0.001). The findings revealed a non-linear relationship between NaOH concentration and moisture content, with 8% being the optimal point. A lower concentration resulted in dense fiber structures that retained water, while a higher concentration led to the formation of cellulose II, which is more hygroscopic. This study highlights the importance of optimizing NaOH concentration in paper production from agricultural waste to achieve the best quality.